Modernism in Buddhist Thoughts – Various Facets of Religion, Rituals, and Reincarnation - Preeti Oza (International Journal of Interreligious and Intercultural Studies, 2022)
When we look at the concept of Modern Buddhism, approximately nine to ten percent of the world is Buddhist. Over half of Chinese Buddhists practise Mahayana. China, Japan, Korea, and Vietnam are the four biggest Buddhist nations. Tibetan Buddhism was accepted by non-Tibetans, mostly in the West, after China colonised Tibet. Almost 488 million Buddhists (9–10%) live in the 21st century. About half of China's population practises Mahayana Buddhism, which is thriving. China, Japan, Korea, and Vietnam have the largest Buddhist populations and influence. After China colonised Tibet, Westerners and others adopted Tibetan Buddhism. In the late nineteenth and early twentieth century, Buddhism responded to shifting circumstances that were impossible in premodern Buddhist religious and cultural world. Western religious, political, and economic principles influenced Buddhist nations that were not subjugated. Asians, Buddhist and non-Buddhist, were influenced by modern rationalistic and scientific ideas, liberal democracy, socialism, and capitalism. Buddhism resurged in India and expanded across Europe and beyond due to Asian Buddhist practises. Scholars most usually refer to forms of Buddhism that originated in the 19th century and combined Buddhist doctrines and practises with key concepts of Western modernity as "Buddhist modernism." They outline the characteristics of Buddhist modernism as being characterised by a deemphasis on texts, logic, meditation, egalitarianism, and increased participation of women and laity, as well as a focus on texts, dogma, clerical hierarchy, "superstition," conventional cosmology, and icon worship. During the time of Christian missionary activity and European colonialism in Buddhist countries, Buddhist modernism began to emerge. It emerged as a form of counterbalance to these pressures as well as an appropriation of Western ideologies, religions, social systems, and lifestyles, leading to the blending of contemporary Western discourses and practises with Buddhism. This paper deliberates on certain global practices of different kinds of Buddhist thoughts